MANAGEMENT OF DIGITAL TRANSFORMATION ON INNOVATION PERFORMANCE IN CHINESE ENTERPRISES: AN EMPIRICAL ANALYSIS - Яо Міньцзян; Аліна Бричко (Економіка та суспільство)
With the rapid rise of the digital economy, digital transformation has become crucial for enterprise development. R&D enterprises face growing innovation pressures and efficiency demands, requiring effective process diagnostics and tailored optimization models. This paper develops a systematic framework for diagnosing R&D processes and proposes an optimization model based on literature analysis and case studies. Using empirical methods, it explores the link between digital transformation and innovation, analyzing data from Chinese A-share listed companies (2018–2023). Findings show digital transformation enhances innovation by optimizing processes and improving efficiency, allowing enterprises to allocate more resources to innovation. This effect is stronger in large enterprises. Despite widespread adoption, patent application analysis suggests room for improvement in innovation performance. This study offers insights into digital transformation’s role in enterprise innovation, guiding firms in enhancing competitiveness.